Monitoring antimalarial resistance: Launching a cooperative effort - Sibley, C; Guerin, P; Ringwald, P (2010)
Current information on efficacy of antimalarials is crucial to provide early warning of resistance. A collaborative effort between the Global Malaria Program of the World Health Organization (WHO) and the WorldWide Antimalarial Resistance Network (WWARN) has recently been launched. The effort is planned as a collaboration with the scientific malaria community to create a global, comprehensive, and inclusive network that will provide quality-assured information on antimalarial drug resistance. © 2010 World Health Organization.